Papua New Guinea : 2010 Article IV Consultation; Staff Report and Public Information Notice. (IMF Staff Country Reports; Country Report, 2010)
This 2010 Article IV Consultation highlights that real activity in Papua New Guinea was relatively unaffected by the global downturn, with growth easing to roughly 5 percent in 2009 from 7 percent in 2008. A number of factors contributed to this favorable outcome. The country's financial sector was insulated from the turmoil in global capital markets and domestic credit continued to grow, albeit at a slower pace than in the preceding few years. Export demand also held up, as stimulus measures in other Asian countries supported demand for commodities, the country's main export.